Penukaran Fail-Fail CAD, Penukaran Fail Gerber - Lily Tiong, Yu Wen (Universiti Sains Malaysia, 2006)
This project is about files conversion of automated optical inspection (AOI) system. The AOI for solder paste inspection and the AOI for pre-reflow inspection are the designated AOI systems where the files conversion of the project take place. The AOI files conversion involved in this project are Gerber file conversion, CAD files conversion and view frames optimization. Gerber file conversion is applied specifically on AOI for solder paste inspection while CAD files conversion is applied on AOI for pre-reflow inspection. Gerber file and CAD files are input files of AOI systems. The files are converted to inspection file through the Gerber file conversion and CAD files conversion. The file conversion of view frames optimization also known as inspection file conversion. It converts the inspection file to image optimization file and it is applied on both the AOI systems mentioned above. View frames optimization is important in improving the performance of the AOI system. The project is developed using the software development tool of Microsoft Visual C# 2005 Express Edition. It is a new programming language that is applied on the .NET Framework and performs well in the AOI files conversion of the project.